Inhibitory effects of olive oil phenolics on invasion in human colon adenocarcinoma cellsin vitro - Hashim, Yumi Zuhanis Has-Yun; Rowland, Ian R.; McGlynn, Hugh; Servili, Maurizio; Selvaggini, Roberto; Taticchi, Agnese; Esposto, Sonia; Montedoro, GianFrancesco; Kaisalo, Leena; Wähälä, Kristiina; Gill, Chris I.R. (Wiley-Liss, Inc., 2007)
Studies in human, animal and cellular systems suggest that phenols from virgin olive oil are capable of inhibiting several stages in carcinogenesis, including metastasis. The invasion cascade comprises cell attachment to extracellular matrix components or basement membrane, degradation of basement membrane by proteolytic enzymes and migration of cells through the modified matrix. In the present study, we investigated the effect of phenolics extracted from virgin olive oil (OVP) and its main constituents: hydroxytyrosol (3,4-dihydroxyphenylethanol), tyrosol (p hydroxyphenylethanol), pinoresinol and caffeic acid. The effects of these phenolics were tested on the invasion of HT115 human colon carcinoma cells in a Matrigel invasion assay. OVP and its compounds showed different dose-related anti-invasive effects. At 25 lg/ml OVP and equivalent doses of individual compounds, significant anti-invasive effects were seen in the range of 45–55% of control. Importantly, OVP, but not the isolated phenolics, significantly reduced total cell number in the Matrigel invasion assay. There were no significant effects shown on cell viability, indicating the reduction of cell number in the Matrigel invasion assay was not due to cytotoxicity. There were also no significant effects on cell attachment to plastic substrate, indicating the importance of extracellular matrix in modulating the anti-invasive effects of OVP. In conclusion, the results from this study indicate that phenols from virgin olive oil have the ability to inhibit invasion of colon cancer cells and the effects may be mediated at different levels of the invasion cascade.